Implementasi Kebijakan Reformasi Birokrasi Melalui E-Procurement Di Bidang Jasa Konstruksi (Studi Pada Kantor Dinas Pekerjaan Umum, Perumahan, Dan Pengawasan Bangunan Kota Malang) - Wildan Nugraha (Jurnal Administrasi Publik, 2015)
Abstract: The Implementation of Bureaucracy Reform Policy Through E-procurement in Construction Service Sector (Study of Public Works, Housing, and Building Inspection Office of The City Goverment of Malang). The Department of Public Works, Housing and Building Inspection of Malang is one of Malang city government institution that implement policies bureaucratic reform in the system of procurement of goods and services electronically ( e –procurement) . E-procurement a system procurement of goods and services that utilize technology and information in the activities that are considered to improve efficiency, effectiveness and transparency in its implementation so as to minimize the possibility of corruption. The study looked at about the implementation of policy reforms in the management in terms of the procurement of goods and services the government based on case on the implementation of the e-procurement in The Department of Public Works, Housing and Building Inspection of Malang by using the method of analysis descriptive approach a qualitative. The implementation of policy reforms through e-procurement resulting in increased efficiency, effectiveness and transparency in the process of the procurement of goods and services as well as to minimize the possibility of irregularities such as corruption in the activities of the procurement of goods and services in Department of Public Works, Housing and Building Inspection of Malang is one of Malang city. Keywords: Policy Implementation, Bureaucracy Reform, E-procurement. Abstrak: Implementasi Kebijakan Reformasi Birokrasi melalui E-procurement di Bidang Jasa Konstruksi (Studi pada Kantor Dinas Pekerjaan Umum, Perumahan, dan Pengawasan Bangunan Kota Malang). Dinas Pekerjaan Umum, Perumahan, dan Pengawasan Bangunan (DPUPPB) Kota Malang merupakan salah satu instansi di pemerintahan kota malang yang melaksanakan kebijakan reformasi birokrasi melalui e-procurement di bidang jasa konstruksi. E-procurement merupakan sistem pengadaan barang jasa yang memanfaatkan teknologi dan informasi dalam kegiatannya yang dinilai dapat meningkatkan efisiensi, efektivitas serta transparansi dalam pelaksanaannya sehingga dapat meminimalisir peluang terjadinya praktik KKN. Penilitian ini mengkaji tentang implementasi kebijakan reformasi birokrasi dalam aspek ketataleksanaan dalam hal proses pengadaan barang jasa pemerintah berdasarkan studi kasus pada pelaksanaan e-procurement di DPUPPB Kota Malang dengan menggunakan metode analisis deskriptif dengan pendekatan kualitatif. implementasi kebijakan reformasi birokrasi melalui e-procurement di bidang jasa konstruksi menghasilkan peningkatkan efisiensi, efektivitas dan transparansi dalam proses pengadaan barang jasa serta mampu meminimalisir peluang terjadinya penyimpangan seperti praktik KKN dalam kegiatan pengadaan barang jasa pemerintah pada DPUPPB Kota Malang. Kata kunci: Implementasi kebijakan, Reformasi Birokrasi, E-procurement.